Learning and Collaboration Technologies Third International Conference, LCT 2016, Held as Part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016, Proceedings - Zaphiris, Panayiotis; Ioannou, Andri (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2016)
This book constitutes the refereed proceedings of the Third International Conference on Learning and Collaboration Technologies, LCT 2016, held as part of the 18th International Conference on Human-Computer Interaction, HCII 2016, in Toronto, Canada, in July 2016, in conjunction with 14 thematically similar conferences. The 1287 papers presented at the HCII 2016 conferences were carefully reviewed and selected from 4354 submissions. The papers cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The papers included in this volume are organized in the following thematic sections: instructional design; interaction techniques and platforms for learning; learning performance; web-based, mobile and ubiquitous learning; intelligent learning environments; learning technologies; collaboration technologies; and cultural and social aspects of learning and collaboration technologies.